Associations between dimensions of empowerment and nutritional status among married adolescent girls in East Africa: a structural equation modelling study - Alison Y. Riddle; Wenshan Li; Zulfiqar A. Bhutta; Carol Vlassoff; Monica Taljaard; Elizabeth Kristjansson; Vivian Welch; George A. Wells (BMC Public Health, 2023)
Abstract Background Empowering adolescent girls is an important component of combating malnutrition in this age group. Because empowerment is multidimensional and context specific, it can be difficult for policymakers and practitioners to target the dimensions of empowerment associated with adolescent girls’ nutrition in a particular setting. This study sought to identify the empowerment dimensions significantly associated with married adolescent girls' nutritional status in East Africa; a region where malnutrition and gender inequality stubbornly persist. Methods We used cross-sectional Demographic and Health Survey (DHS) data from Ethiopia (2016), Kenya (2014), Tanzania (2015–16) and Uganda (2016) to construct and test theoretically informed structural equation models of the relationship between six dimensions of empowerment and BMI-for-age and haemoglobin levels for married adolescent girls aged 15–19 years. Results Our models were found to be a good fit for the data. Married adolescent girls’ access to information, measured by their education level and mass media use, was directly and positively associated with their BMI-for-age (p < 0.05). Asset ownership, measured by owning a house or land alone or jointly, was directly and positively associated with haemoglobin (p < 0.05) and reduced odds of being moderately to severely anemic. Rejecting justifications for intimate partner violence, a measure of respondents’ intrinsic agency, was directly and positively associated with the odds of being overweight or obese. Adolescent girls’ level of empowerment across all dimensions had a direct relationship with their country of residence and household wealth. Conclusions Our findings suggest that investment in girls’ access to information through education and mass/social media and their economic empowerment may be important contributors to their overall empowerment and nutritional status. However, caution is needed as greater autonomy may contribute to increased consumption of unhealthy foods that can contribute to overweight and obesity. Strategies to empower married adolescent girls should be tailored to their specific circumstances. There is an urgent need for better data on adolescent empowerment and health, including increased research into age-, sex- and gender-appropriate empowerment measures and longitudinal data to assess causality. The use of statistical models should be complemented by robust qualitative research to further results interpretation.